Experimental investigation on an auto-cascade quasi two-stage compression heat pump system. (25th January 2023) - Cui, Mengdi; Cheng, Zuo; Wang, Baolong; Wei, Falin; Shi, Wenxing
Highlights: A novel auto-cascade quasi two-stage compression heat pump system is proposed. Experimental research was conducted on the novel system with HFC32/HFO1234ze(E). The novel system has a 6.2–9.0 % higher COP than the flash tank system. The novel system has a 1.8–3.5% higher COP than the internal heat exchanger system. Abstract: Refrigeration and heat pump systems consume approximately 20 % of global electricity. The (quasi) two-stage compression and auto-cascade cycle configuration are effective approaches to save energy for vapor compression refrigeration and heat pumps because the former can reduce throttling irreversibility and the latter takes advantage of the concentration separation of zeotropic refrigerants to reduce the pressure lift of the system. Accordingly, a new auto-cascade quasi two-stage compression system (ACQT) used for building heating is proposed in this study. An experimental setup was built. The performance of the proposed system charging with a 0.5/0.5 mole fraction of HFC32/HFO1234ze(E) was experimentally explored by comparing it with a quasi two-stage compression system with an internal heat exchanger (IHXQT) and that with a flash tank (FTQT). The results indicate that the ACQT improves the coefficient of performance (COP) by 6.2–9.0 % compared to the FTQT while maintaining the same heating capacity. Moreover, the ACQT achieves a 1.8–3.5 % higher COP than the IHXQT while maintaining the same heating capacity.